Social Networks and Students' Orthography - E. Azizovic; M. Kacka; M. Saracevic; A, Bihorac (University of Sofia, 2017)
The paper studied spelling and technical errors of students on social networks (facebook, twitter, e-mail). Social networks have over the last decade become the primary means of communication, which have more than ever made real the idea of "one world - one village". Their usage is in the most part based on language, i.e. on the writing itself and reading of the same as its most complex parts. New aspects of the use of writing, which exclude handwriting, are already using some new writing platform, such as keyboards, smart - touch surfaces, etc., provide new opportunities for redefining, as well as challenges for the writings. This paper aims to give a modest contribution in this direction.